Life Course Impact of Glucocorticoids During Pregnancy on Muscle Development and Function - Liu, Yang; Ding, Qiyue; Guo, Wei (Frontiers in Animal Science, 2021)
Maternal stress, such as maternal obesity, can induce severe gestational disease and hormonal disorder which may disrupt fetal organ maturation and further cause endangered early or future health in offspring. During fetal development, glucocorticoids are essential for the maturation of organ systems. For instance, in clinical applications, glucocorticoids are commonly utilized to pregnant women with the risk of preterm delivery to reduce mortality of the newborns. However, exposure of excessive glucocorticoids at embryonic and fetal developmental stages can cause diseases such as cardiovascular disease and muscle atrophy in adulthood. Effects of excessive glucocorticoids on human health are well-recognized and extensively studied. Nonetheless, effects of these hormones on farm animal growth and development, particularly on prenatal muscle development, and postnatal growth, did not attract much attention until the last decade. Here, we provided a short review of the recent progress relating to the effect of glucocorticoids on prenatal skeletal muscle development and postnatal muscle growth as well as heart muscle development and cardiovascular disease during life course.